2021
DOI: 10.1200/jco.2021.39.6_suppl.465
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of microsatellite instability (dMMR/MSI-H) and mutational landscape in a large contemporary cohort of upper tract urothelial cancer (UTUC) patients.

Abstract: 465 Background: UTUC is a rare genitourinary malignancy and a number of studies, limited by small sample sizes, have attempted to characterize its mutational landscape. Because immunotherapy is commonly used for this disease type, we evaluated the prevalence of microsatellite instability and characterized the mutational landscapes of UTUC in a large contemporary patient cohort. Methods: UTUC tumor samples were analyzed using next generation sequencing (NGS) (NextSeq, 592 gene panel) or whole exome sequencing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…In addition, somatic mutations in ARID1A, CDC73, and SMARCA4 gene were co-occurrent with germline mutations of the MMR pathway (Fig. 4B); previous studies have found that mutations in ARID1A [53], CDC73 [54], and SMARCA4 [55] are enriched in microsatellite instable tumors, which supports our findings and demonstrates these genes may be the targets of MMR deficiency. Germline variants can also affect the distribution of somatic mutation loci.…”
Section: Germline Variants Impact On Somatic Mutation Profilesupporting
confidence: 91%
“…In addition, somatic mutations in ARID1A, CDC73, and SMARCA4 gene were co-occurrent with germline mutations of the MMR pathway (Fig. 4B); previous studies have found that mutations in ARID1A [53], CDC73 [54], and SMARCA4 [55] are enriched in microsatellite instable tumors, which supports our findings and demonstrates these genes may be the targets of MMR deficiency. Germline variants can also affect the distribution of somatic mutation loci.…”
Section: Germline Variants Impact On Somatic Mutation Profilesupporting
confidence: 91%
“…Unlike rare germ line diseases in western countries, the UTUC carcinogenic mechanism had been reported with chronic exposure to aristolochic acid (AA) that induces the TP53 fingerprint mutation. [32][33][34][35][36][37] Recent fundamental research has demonstrated that tumors harboring AA mutational signatures are correlated with a higher tumor mutational burden and more predicted tumor-associated neoantigens, implying the potential efficacy of IO in various types of solid tumors. [38][39][40][41][42] By comprehensive whole genomic sequencing analysis of 90 UTUC patients, Lu et al found that UTUC with AA mutational signature had a significantly higher neoantigen burden, increasing tumor-infiltrating lymphocytes and associated with better cancer-specific survival and metastasis-free survival.…”
Section: Discussionmentioning
confidence: 99%
“…UTUC is well known for its association with Lynch syndrome and microsatellite instability. Unlike rare germ line diseases in western countries, the UTUC carcinogenic mechanism had been reported with chronic exposure to aristolochic acid (AA) that induces the TP53 fingerprint mutation 32–37. Recent fundamental research has demonstrated that tumors harboring AA mutational signatures are correlated with a higher tumor mutational burden and more predicted tumor-associated neoantigens, implying the potential efficacy of IO in various types of solid tumors 38–42.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of function in the MMR system, either caused by an inherited mutation or a sporadic event, results in microsatellite instability (MSI) throughout the genome [31]. MSI have been found between 3.9% to 20% in UTUC as compared to <1% in UBC [32,33]. High MSI is correlated with a better prognosis, particularly in patients younger than 71 years old with T2-T3N0M0 tumors [34].…”
Section: The Molecular Landscape Of Utucmentioning
confidence: 99%